2019
DOI: 10.1186/s13561-019-0255-5
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance coverage, type of payment for health insurance, and reasons for not being insured under the National Health Insurance Scheme in Ghana

Abstract: BackgroundGhana’s National Health Insurance Scheme has improved access to care, although equity and sustainability issues remain. This study examined health insurance coverage, type of payment for health insurance and reasons for being uninsured under the National Health Insurance Scheme in Ghana.MethodsThe 2014 Ghana Demographic Health Survey datasets with information for 9396 women and 3855 men were analyzed. The study employed cross-sectional national representative data. The frequency distribution of socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 45 publications
9
28
1
Order By: Relevance
“…The findings of the study revealed that about two thirds of women are covered by health insurance. This is consistent with reports from a previous study regarding the proportion of the population actively enrolled in the national health insurance scheme [ 25 ]. Moreover, our findings on pro-rich out-of-pocket expenditure were consistent with the results from previous studies conducted in resource-poor settings that respondents from higher household wealth quintiles were more likely to have out-of-pocket health expenditures compared with their counterparts from poor household wealth quintiles [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the study revealed that about two thirds of women are covered by health insurance. This is consistent with reports from a previous study regarding the proportion of the population actively enrolled in the national health insurance scheme [ 25 ]. Moreover, our findings on pro-rich out-of-pocket expenditure were consistent with the results from previous studies conducted in resource-poor settings that respondents from higher household wealth quintiles were more likely to have out-of-pocket health expenditures compared with their counterparts from poor household wealth quintiles [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is similar to previous studies that reported that women of reproductive age were more likely to obtain more information on health insurance than men [58,59]. Even though women were more likely to lack a support system and have poor participation in economic activities to purchase health insurance plans, studies have reported that women were more willing to pay to become active health insurance subscribers [58,59]. The association between gender and health insurance is similar but more complex in other research.…”
Section: Discussionsupporting
confidence: 92%
“…The direction of influence of gender on health insurance uptake is varied in the literature; one study did not find significant differences in health insurance coverage based on sex in Kenya [55][56][57]. Conversely, few studies have shown that decreased insurance uptake among males is a result of them seeming to be risk-takers [52,53], while further studies have reported that increased health insurance uptake by women was as a result of greater needs for healthcare services [58,59]. However, the decrease in women's uptake of health insurance in both countries may be associated with the low socio-economic status of women relative to men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Inadequate claim returns, poor accountability and non-transparent operations hinders the uptake of health insurance. 18 In Indian studies, a scant that is, 34% of the participants who did not have health insurance were willing to pay for any health insuance. 5 Previous research in LMICs suggests that financial status of household is positively associated with WTP.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%